Pengaruh Reputasi Kap Dan Profitabilitas Terhadap Audit Delay - Aufa Nizar Arsalan; Indupurnahayu .; Muhammad Nur Rizqi (Jurnal Akuntansi Keuangan dan Bisnis, 2026)
This study aims to determine the influence of the Accountant Public Firm reputation on Audit Delay, influence profitabilityis reflected in ROA on Audit Delay, as wellas the influence of the Accountant Public Firm reputation and profitability is reflected in ROA on Audit Delay. This research uses descriptive quantitative research consisting of 15 banking companies from 42 populations listed on the IDXin 2021-2023 which were selected based on the Purposive Sampling method. Data used in the form of the Audited Financial Statements. The analytical method usedis Descriptive Statistics, Classical Assumption Test, Multiple Linear Regression Analysis. Data processing was performed using the software program Statistical Product and Service Solution (SPSS). These results indicate that the Variable of Accountant Public Firm reputation and Variable of Profitability reflected in returnon assets have negative influence on Audit Delay. Hypothesis test results simultaneously concluded that two independent variables jointly have negative influence on Audit Delay.